Soil seed bank and the effect of needle litter layer on seedling emergence in a tropical pine plantation - Andrea Bueno; Zdravko Baruch (Revista de Biología Tropical, 2011)
The soil seed bank is the basis for community establishment and permanence and plays a primary role in natural restoration of degraded or altered ecosystems. As part of a restoration project, this study aimed to quantify the soil seed bank and to evaluate the effect of the needle litter layer on seedling emergence. Soil samples from a pine plantation were collected at random in the field and set to germinate in a greenhouse. Half of them were covered by a 6cm layer of dead pine needles simulating field conditions. in the field, 20x20cm plots were established, half were left intact and half were cleaned from the litter needles. All four treatments had 15 replicates and seedling emergence was recorded during six months. Soil seed bank density was 1 222/m² from 17 morphotypes. in the field, the number of morphotypes and seedlings was only 9% and 6% respectively, of those emerged in the greenhouse, possibly due to watering and lack of predation in the latter. in both cases, herbs and graminoids were the dominant emerging seedlings, making up to 70-90% of the total. The needle layer didn’t prevent seeds from reaching the soil but strongly reduced (>50%) seedling emergence, although high variability within treatments resulted in no statistically significant differences. These results show that the needle layer hinders germination and/or emergence of seedlings from the seed bank. its removal may be a recommended technique to accelerate natural restoration in pine plantations. Rev. Biol. Trop. 59 (3): 1071-1079. Epub 2011 September 01 El banco de semillas del suelo es la base para el establecimiento y la permanencia de una comunidad y desempeña un papel fundamental en la restauración natural de los ecosistemas degradados o alterados. Como parte de un proyecto de restauración, este estudio tuvo como objetivo cuantificar el banco de semillas del suelo y evaluar el efecto de la capa de hojarasca de pino sobre la emergencia de las plántulas. Las muestras de suelo de la plantación de pinos fueron recolectadas al azar en el campo y se pusieron a germinar en un invernadero. La mitad de ellas estaban cubiertas por una capa de 6cm de hojarasca simulando condiciones de campo. En el campo se establecieron parcelas de 20x20cm, la mitad se dejaron intactas y la otra mitad se limpiaron de la hojarasca. Para los cuatro tratamientos se realizaron 15 repeticiones y la emergencia de plántulas se registró durante seis meses. La densidad del banco de semillas del suelo fue de 1 222/m² de 17 morfotipos. En el campo, el número de morfotipos y plántulas fue sólo de 9% y 6% respectivamente, de los que emergieron en el invernadero, posiblemente debido al riego y la falta de depredación. En ambos casos las plántulas dominantes fueron las hierbas y gramíneas, alcanzando el 70-90% del total. La capa de hojarasca no impidió que las semillas llegaran al suelo, pero se presentó una emergencia de plántulas muy reducida (>50%), debido a la alta variabilidad de los tratamientos no se produjeron diferencias estadísticamente significativas. Estos resultados muestran que la capa de hojarasca impide la germinación y/o la emergencia de las plántulas del banco de semillas del suelo. Su eliminación puede ser una técnica recomendada para acelerar la restauración natural en las plantaciones de pino.